2020
DOI: 10.1021/acs.inorgchem.0c01241
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations of Lu2C84: Unexpected Impact of Metal Electronic Configuration toward the Metal–Metal σ-Bond in Fullerene

Abstract: Recent experimental works recovered multiformity of lutetium-involved dimetallofullerenes. On the basis of density functional theory (DFT) combined with statistical thermodynamic analyses, the relative stabilities of Lu 2 C 84 dimetallofullerene were clarified. Besides the experimentally acknowledged Lu 2 @ D 2d (51591)-C 84 and Lu 2 @C 2v (51575)-C 84 , another four isomers metallofullerenes, Lu 2 @C 1 (51580)-C 84 , Lu 2 C 2 @C s (39715)-C 82 , Lu 2 C 2 @C 3v (39717)-C 82 , and Lu 2 C 2 @C 2v (39718)-C 82 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“…However, only a few cases have been found experimentally or theoretically after considerable efforts to explore endo-metal-metal bonds in fullerene cages. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] An unexpected challenge in determining endo-metal-metal bonding in fullerene cages by X-ray crystallography is posed by severe disorder in the crystal structures, especially for metallic endo-clusters, and there can be up to tens of disordered sites when determining endo-metal atoms in a fullerene cage. Therefore, searching for an example system with less metallic disorder is the key to precisely elucidating the nature of endo-metal-metal bonds.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few cases have been found experimentally or theoretically after considerable efforts to explore endo-metal-metal bonds in fullerene cages. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] An unexpected challenge in determining endo-metal-metal bonding in fullerene cages by X-ray crystallography is posed by severe disorder in the crystal structures, especially for metallic endo-clusters, and there can be up to tens of disordered sites when determining endo-metal atoms in a fullerene cage. Therefore, searching for an example system with less metallic disorder is the key to precisely elucidating the nature of endo-metal-metal bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest-energy isomer of the Lu 2 C 2 @C 84 is Lu 2 C 2 @ D 2 d (51591)-C 84 with the relative energy of 18.9 kcal·mol –1 higher than that of the lowest-energy isomer of the Lu 2 @C 86 series. The D 2 d (51591)-C 84 cage is the pristine cage of the Lu 2 C 84 series . Other Lu 2 C 2 @C 84 isomers have much larger relative energies of over 28.3 kcal·mol –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous theoretical studies have discovered geometrical relationships among the pristine cages of EMF isomers, , which are significant for research of the fullerene formation mechanism. Our study of Lu 2 C 84 revealed geometrical relationships among stable Lu 2 @C 84 and Lu 2 C 2 @C 82 through SWT and C 2 loss/insertion. , In fact, a larger geometrical relationship diagram among the experimentally detected and theoretically predicted Lu 2 C 2 n , including the Lu 2 C 86 series in this study, has been found. As shown in Figure , the C s (63750)-C 86 and C s (63757)-C 86 cages are related by one-step SWT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations